2006
DOI: 10.1128/jvi.01041-06
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase A2 Activity-Dependent Stimulation of Ca 2+ Entry by Human Parvovirus B19 Capsid Protein VP1

Abstract: Recent reports demonstrated an association of human parvovirus B19 with inflammatory cardiomyopathy (iCMP), which is accompanied by endothelial dysfunction. As intracellular Ca 2؉ activity is a key regulator of cell function and participates in mechanisms leading to endothelial dysfunction, the present experiments explored the effects of the B19 capsid proteins VP1 and VP2. A secreted phospholipase A2 (PLA2)-like activity has been located in the VP1 unique region of the B19 minor capsid protein. As PLA2 has re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
40
0
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 91 publications
1
40
0
4
Order By: Relevance
“…Further attempts to knock out the (pA)p sites were not tried since this region is in the coding region for the VP1 unique part. In all parvoviruses except Aleutian mink disease virus, the minor structural protein, VP1, possesses motifs that have PLA 2 activity shown to be essential for nuclear entry of the virus during infection (22,27,42,54,67). The HDXXY motif that was found in the catalytic site of sPLA 2 s (21) is also predicted to be present in the VP1u of MVC (58).…”
Section: Discussionmentioning
confidence: 99%
“…Further attempts to knock out the (pA)p sites were not tried since this region is in the coding region for the VP1 unique part. In all parvoviruses except Aleutian mink disease virus, the minor structural protein, VP1, possesses motifs that have PLA 2 activity shown to be essential for nuclear entry of the virus during infection (22,27,42,54,67). The HDXXY motif that was found in the catalytic site of sPLA 2 s (21) is also predicted to be present in the VP1u of MVC (58).…”
Section: Discussionmentioning
confidence: 99%
“…These studies also suggest that prior to escaping the endosome, the virion must undergo conformational changes, leading to the exposure of the unique N terminus of Vp1 and the N terminus of Vp2 required for endososmal escape and nuclear entry (6, 9, 19, 33,35). The unique N terminus of Vp1 contains a conserved PLA2 domain (8,15,18,28,52) that is essential for infectivity and is thought to be required for endosomal escape. A suggestion that the N termini of Vp1 are located within the virion and become surface exposed naturally within the cell, via an induced conformational change, is consistent with the observation that while intact capsids do not have PLA2 activity, heat or acidic-pH treatment of virions elicits this function (37,52).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that active persistent B19V-infection is responsible for triggering inflammatory response in the myocardium [18] . Recently, we demonstrated that B19V and the viral proteins of B19V play an important pathophysiological role in modulating inflammatory signaling, regulation of pro-apoptotic processes and modulation of the intracellular Ca 2+ -activity leading to endothelial dysfunction [26,33,34] . It is important to note that B19V DNA is more frequently found in EMBs of patients with chronic myocarditis (59.6%) compared to control cardiac tissue samples from individuals without heart failure (7.7%), a finding consistent with other reports [2,35] .…”
Section: Discussionmentioning
confidence: 99%